2019
DOI: 10.1007/s11145-019-09951-w
|View full text |Cite
|
Sign up to set email alerts
|

Explicit reading strategy instruction or daily use of strategies? Studying the teaching of reading comprehension through naturalistic classroom observation in English L2

Abstract: Research suggests that developing deep understanding of text requires sustained emphasis on reading comprehension instruction and scaffolded strategy practices. However, although research has shown explicit teaching of reading comprehension strategies to be effective, we know little about whether strategy instruction and use are part of "daily life" in classrooms (Pearson, & Cervetti, 2017). The present study analyses 60 video recorded English as a second language (L2) lessons in seven lower secondary schools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 30 publications
(53 reference statements)
4
70
0
9
Order By: Relevance
“…Interestingly, although this teacher discouraged the oral use of multilingual resources, she encouraged the students’ use of bilingual (English–Norwegian) dictionaries to scaffold their English reading comprehension (Brevik, 2019a). Thus, whereas teachers in most high‐frequency English classrooms briefly affirmed students’ language resources, this teacher (S02) explicitly prompted students not to use languages other than English.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, although this teacher discouraged the oral use of multilingual resources, she encouraged the students’ use of bilingual (English–Norwegian) dictionaries to scaffold their English reading comprehension (Brevik, 2019a). Thus, whereas teachers in most high‐frequency English classrooms briefly affirmed students’ language resources, this teacher (S02) explicitly prompted students not to use languages other than English.…”
Section: Resultsmentioning
confidence: 99%
“…The same study found that the highest PLATO scores were found in the domain Classroom Environment, indicating that disciplinary problem were highly infrequent. A study of Norwegian English L2 showed that while strategy use occurred frequently, explicit instruction of strategies was very scarce (Brevik, 2019).…”
Section: Observing Teaching Qualitymentioning
confidence: 99%
“…Leseren må bevisst anvende det vi kan kalle kognitive teknikker før lesing, underveis eller etter lesing, eller i alle tre fasene, samtidig som formålet med lesingen er i fokus (Paris, Wasik & Turner, 1991). De strategiske leserne overvåker leseprosessen, oppdager hull i forståelsen og bruker reparasjonsstrategier hvis det trengs (Baker & Brown, 1984;Coiro & Dobler, 2007); de tar beslutninger om hvilken strategi de skal bruke, i hvilke situasjoner de skal bruke den, og hvordan de kan tilpasse den til en bestemt tekst (Paris, Lipson & Wixson, 1983), og endrer strategier for å passe til forskjellige typer tekster og forskjellige formål. Forståelse av hvorfor og når man skal anvende forskjellige strategier -såkalt situasjonsbetinget kunnskap -er altså viktig for strategibruk.…”
Section: Strategier For Leseforståelseunclassified